PHYTOPLANKTON COMMUNITY STRUCTURE IN MANGROVE WATERS OF RAWA RIVER VILLAGE, SIAK PROVINCE, RIAU - Putri Amelia Yolanda; Adriman Adriman; Nur El Fajri (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTMangrove river swamp village is one of the mangroves in Siak Regency, Riau Province. This study aims to determine the structure of the phytoplankton community in the mangrove ecosystem, which was conducted in April 2019. Samples were taken 3 times, once / week, in 3 different regions. The results found that there were 19 species of phytoplankton in mangrove waters of swamp river villages. Phytoplankton consists of 4 (four) classes, namely: Bacillariophyceae (14 types), Chlorophyceae (1 type), Cyanophyceae (3 types), and Xantophyceae (1 type). The abundance of phytoplankton species in the waters ranges from 5375 -13550cells / L. The results of the phytoplankton species diversity index (H ') in the mangrove waters of Sungai Rawa Village ranged from 2.9323 – 3.8107, the dominance index (C) ranged from 0.0757 -0.1365and the uniformity index (E) ranged from 0.7174 - 0.9323. Water quality in the mangrove waters of Sungai Rawa Village is a temperature of 29-30ºC, brightness 52-76 cm, pH 7, salinity 24.33-26.33‰, dissolved oxygen 5.03-6.13 mg / L, free carbon dioxide 2.50 -3.28 mg / L, nitrate 0.08-0.16 mg / L and phosphate in the range 0.09-0.17 mg / L.Keywords: community structure, mangrove ecosystems, Bacillariophyceae